The supply-side IT outsourcing competencies and relationship exchange in Malaysia - Arshad, Yusri; Ahlan, Abdul Rahman; Hussein, Ramlah (WSEAS Press, 2008)
IT outsourcing (ITO) has experienced a considerable growth in recent years, so much so that some authors suggest we find ourselves in the outsourcing era. ITO growth seems to be guaranteed at least in the near future. Many past researches on IT outsourcing were done in North America, Europe and Australasia contexts with little evidence from developing countries perspectives [13, 26]. IT outsourcing relationship researches revealed its importance in improving the success of IT outsourcing arrangements. Many researches on relationship, however, were investigated from demand-side perspectives. Hence, it is the aim of this study to complement these one-dimensional findings by investigating the IT outsourcing relationship exchange from service providers’ perspectives in Malaysian context. This report presents the first phase qualitative findings of an on-going research on IT outsourcing competencies and relationship. The study comprises three phases: 1) a focus group and in-depth interviews; 2) mass survey; and 3) final group discussion. The authors have arranged an expert focus group deliberating on the emerging issues and subsequently interviewed five senior executive managements in the service provider firms to explore further on key variables. The unstructured interviews were recorded and transcribed and analysed based on Miles and Huberman (1994) recommendations. The study found that all the variables are, in practice, important determinants of successful outsourcing projects as claimed by many other researches in the western context. The ranking of the determinants or factors, however, were of varying disputes depending on the types of ITO configurations the parties entered into.